Cyclic voltammetric studies of indium tin oxide electrode modified with Fe2+ and Cu2+ birnessite-type manganese oxide for the oxidation of glutathione - Enot, Melania Manginsay (Animo Repository, 2007)
The modified birnessites, Cu-OL-1 and Fe-OL-1 in indium tin oxide (ITO) and the carbon paste electrodes have been constructed and electrochemically studied including its catalytic properties. The electrochemical studies employed cyclic voltammetry using the modified electrodes as indicator electrode with aqueous solutions of 0.10M NaH2PO4 / Na2HPO4 buffer (pH=7.0), 0.10M KNO3, 0.10M KCl and 0.045 M Na2HPO4 (pH =7.0) as the various supporting electrolytes against Ag / AgCl reference electrode. The Cu-OL-1 modified indium tin oxide electrode showed a quasi-reversible reactions in 0.10M NaH2PO4 / Na2HPO4 buffer (pH=7.0), 0.10M KNO3, and 0.045 M Na2HPO4 (pH =7.0); and a well-defined irreversible cathodic waves in 0.10M KCl. The Fe-OL-1 modified indium tin oxide electrode also produced well-defined anodic and cathodic peaks in the potential range being studied using 0.10M NaH2PO4 / Na2HPO4 buffer (pH=7.0) and 0.045M Na2HPO4 (pH=7.0). However, it did not produce the same voltammetric peaks in 0.10M KNO3 and 0.10M KCl. The diffusion coefficients of the electroactive species were determined. The values showed an appreciable increase with the increase in scan rates which suggests that the electrochemical reactions involving the electroactive species Cu2+ and Fe2+ were diffusion-controlled. The cyclic voltammetric technique with modified carbon paste electrode was investigated but no voltammetric peak was observed. The electrocatalytic oxidation of glutathione was manifested in Cu-OL-1 and Fe-OL-1 modified indium tin oxide electrode (ITO). The evidence of this catalytic xviii activity was the increase in current response of 95.95% at the Cu-OL-1 modified ITO and 89.74% at the Fe-OL-1 modified ITO in the presence of glutathione. The electrocatalytic reactions by the modified electrodes on the oxidation of glutathione were controlled by diffusion.